Identifying the guilty word: Simultaneous versus sequential lineups for DRM word lists. - Finley, Jason R.; Wixted, John T.; Roediger III, Henry L. (Memory & Cognition, 2020)
Recent research in the eyewitness identification literature has investigated whether simultaneous or sequential lineups yield better discriminability. In standard eyewitness identification experiments, subjects view a mock-crime video and then are tested only once, requiring large samples for adequate power. However, there is no reason why theories of simultaneous versus sequential lineup performance cannot be tested using more traditional recognition memory tasks. In two experiments, subjects studied DRM (Deese-Roediger-McDermott) word lists (e.g., bed, rest, tired,...) and were tested using "lineups" in which six words were presented either simultaneously or sequentially. A studied word (e.g., tired) served as the guilty suspect in target-present lineups, unstudied related words (e.g., nap) served as fillers in target-present and target-absent lineups, and critical lures (e.g., sleep) were included in some target-present and target-absent lineups as well, to serve as attractive alternatives to the target word (or suspect). ROC analyses showed that the simultaneous test format generally yielded superior discriminability performance compared to the sequential test format, whether or not the critical lure was present in the lineup.